THE USAGE OF WARD AND PEPPARD METHOD IN IS/IT STRATEGIC PLAN COMPILATON IN DISHUBKOMINFO EAST LAMPUNG - Abdul Lathif Sampurna; Abdi Darmawan; Handoyo Widi Nugroho (Proceeding International Conference on Information Technology and Business, 2015)
Dishubkominfo in running the coordination task in Nexus,Communication and Informatics field must charged towork fast. Therefore, the support from the reliableinformation technology (IS/IT) is really needed. To makesure the usage of IS/IT actually support the purpose ofgovernment administering, with noticing the efficiency theusage of resources and the management of risk that relatedto it, it required strategic planning related to IS/IT, in thisdocument called Strategic Planning IT/IS.The methodology that used in preparation of documentusing reference that developed by Ward and Peppard.Analysis method that used includes SWOT analysis, CSF,Value Chain, McFarlan Strategic Grid, BalancedScorecard. The result that achieved in this thesis isstrategic plan framework that include system informationstrategy, information technology and IT/IS managementintegrated and portfolio and roadmap from 2015 until2019.KEYWORDS : Strategic Plan IT/IS, Planning, Ward andPeppard, Dishubkominfo